2015
DOI: 10.4238/2015.september.8.10
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low temperatures on BAX and BCL2 proteins in rats with spinal cord ischemia reperfusion injury

Abstract: ABSTRACT. We evaluated changes in BAX and BCL2 expression levels after spinal cord ischemia/reperfusion injury (SCII) and hypothermia during operations in rats. Eighty rats were divided into four groups: Group A (N = 20, 18°C); Group B (N = 20, 28°C); Group C (N = 20, room temperature); and Group D (N = 20, sham operation control). Spinal cord ischemia was induced for 90 min. Hypothermia was induced 15 min before, and maintained during ischemia, followed by heating to normothermia for 30 min after reperfusion.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…Hypothermia thus might attenuate hypoxia‐induced apoptosis and therefore apoptotic markers were increased in retinal explants treated with 30°C of hypothermia, whereas 20°C hypothermia has a stronger neuroprotective effect than 30°C and might not only attenuate but suspend apoptosis. Again, this effect was also found in a spinal cord ischemia reperfusion injury study …”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Hypothermia thus might attenuate hypoxia‐induced apoptosis and therefore apoptotic markers were increased in retinal explants treated with 30°C of hypothermia, whereas 20°C hypothermia has a stronger neuroprotective effect than 30°C and might not only attenuate but suspend apoptosis. Again, this effect was also found in a spinal cord ischemia reperfusion injury study …”
Section: Discussionsupporting
confidence: 74%
“…Again, this effect was also found in a spinal cord ischemia reperfusion injury study. 40 The neuroprotective effect of hypothermia was also visible under normoxic control conditions. The neuronal marker Thy1 was significantly increased and the apoptotic Bax/Bcl-2 mRNA ratio was decreased in retinal explants treated only with hypothermia of 20 C compared to standard culture conditions of 37 C. Taken together, hypothermia is a potent protection against retinal hypoxia, defending the hypoxiatreated retinal explants against retinal thinning, decreased RGC survival, increased RGC death, gliosis and loss of spontaneous RGC activity.…”
Section: Discussionmentioning
confidence: 96%
“…Spinal cord I/R injury occurs in up to one-fifth of high-risk patients [ 2 ]. Although there are some potential measures that have shown promise (such as controlled hypothermia and hyperbaric oxygen therapy) [ 3 , 4 ], there is an urgent need to develop further neuroprotective strategies to target this devastating complication.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, low temperature has a protective effect on SCIRI, as has been reported in rat model [26,27]. Recently, Zhu et al [28] showed that hypothermia treatment can reduce neurons apoptosis and improve locomotion function after spinal cord ischemia injury in rats, and mechanisms underlying these effects are associated with the inhibition of the expression of Bcl-2 associated X (BAX) protein and the activation of B-cell lymphoma-2 (Bcl-2) protein, both crucial plyers Bcl-2 in cell apoptosis. It has been reported that low temperature treatment can protect the integrity of the BSCB.…”
Section: Hypothermia Treatmentmentioning
confidence: 79%